PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN TEH PUCUK HARUM DI KOTA BEKASI - Anjasmara, Rengga; Winarso, Widi; Putra, Christophorus Indra Wahyu; Komariah, Neng Siti; Anas, Haryudi (SINERGI : Jurnal Riset Ilmiah, 2025)
The influence of brand image and product quality on purchasing decisions for Pucuk Harum Tea in Bekasi City. This research uses a quantitative approach through the Accidental Sampling technique for sampling. A total of 108 people in the city of Bekasi focusing on Medan Satria sub-district who had used Teh Pucuk Harum products were the research samples. Data examination uses the Partial Least Square (PLS) SEM method on SmartPLS 4.0. The research findings reveal the following: 1.) Brand Image has a significant influence on Purchasing Decisions, 2.) Product Quality has a significant influence on Purchasing Decisions.